The Politics and Poetics of Oppression in Caryl Churchill’s Seven Jewish Children - Abdel Aziz, Amal (International Journal of Language and Literary Studies, 2020)
Caryl Churchill is one of the leading contemporary British playwrights. Because of the Israel military strike on Gaza in early 2009, she wrote her short poetic play, Seven Jewish Children, which densely explores modern Jewish history, from the time of pre-holocaust Europe up to the current struggles between Israel and Palestinian militant organizations. The stimulating dynamism of Churchill’s historical chronicle is that though it introduces the past suffering of the Jews, it exposes their moral insincerity when it comes to labeling the current brutal actions performed by the state of Israel against Palestinian civilians. Employing a descriptive-analytical approach, this paper examines the play as a poetic narrative representing a pattern of reversed oppression in which contemporary Israelis, descendants of former victims of the Nazi, have inherited the legacy of the Holocaust and are deemed accountable for the ruthless violence perpetrated on the Arab residents of the occupied land.